Phenotypes, natural history and barcodes unveil cryptic species within the Caribbean Metalmark Dianesia carteri (Holland) (Lepidoptera: Riodinidae) - Álvarez, Yosiel; Núñez, Rayner; Magaldi, Luiza De Moraes; Matthews, Deborah; Freitas, André Victor Lucci; Espeland, Marianne (Zootaxa, 2025)
The butterfly genus Dianesia Harvey & Clench, 1980 is the only known representative of the family Riodinidae in the West Indies with a single described species containing two subspecies, represented by rare, little-known populations occurring only in the Bahamas and Cuba. Until now, the genus has been regarded as monotypic, but differences in morphology, DNA barcodes and life history suggest that it contains multiple cryptic species. Our assessment led to recognize the existence of at least nine species within Dianesia: Dianesia carteri (Holland, 1902), Dianesia ramsdeni (Skinner, 1912) (previously regarded as a subspecies of the first), Dianesia galindoensis Barro, Hernández & Torres, 2025, and the newly herein described Dianesia aberrans sp. nov., Dianesia sheylae sp. nov., Dianesia alayoi sp. nov., Dianesia flammata sp. nov., Dianesia abscondita sp. nov. and Dianesia serpentinicola sp. nov. These species remained unnoticed due to their superficial resemblance and lack of information about their biology, but can be differentiated by a combination of their DNA barcodes, wing length and shape, and elements of the color pattern, particularly the forewing postdiscal white band. Genitalia, habitat, host plant, and larval morphology also serve to differentiate the species. Bayesian and maximum likelihood COI gene trees recovered a similar topology in which all species are reciprocally monophyletic except for D. alayoi nested inside D. flammata. Species delimitation analyses supported the described species, including those that are not monophyletic, and suggested the presence of three additional species, but we regard them as artifacts produced by specimens with slightly different barcodes. Future research employing more genetic and ecological data is necessary to clarify the relationships among these species, as well as to understand their biogeographical history, ecology, and behavior, and to provide baseline knowledge for their conservation.